Correlating estrogen replacement therapy and temporomandibular disorders: a comprehensive review following PRISMA principles and cochrane handbook for systematic reviews of interventions - Mohammad Khursheed Alam; Maysara Adnan Ibrahim; Manal Jamil Almaslamani; Musab Hamed Saeed; Yuliia Siurkel; Vincenzo Ronsivalle; Marco Cicciù; Giuseppe Minervini (BMC, 2024)
Abstract Background Estrogen replacement therapy (ERT) is a common hormonal treatment for postmenopausal women, aimed at alleviating menopausal symptoms and reducing the health risks associated with estrogen deficiency. However, the impact of ERT on temporomandibular disorders (TMDs) remains unclear. This systematic review aims to evaluate the relationship between ERT and TMDs, including TMD occurence, pain, and associated symptoms. Methods A comprehensive search of seven electronic databases was conducted using predefined search terms and Boolean operators. Inclusion criteria encompassed studies examining the association between ERT and TMDs. Two independent reviewers screened the identified articles, extracted data, and assessed the risk of bias using the RoB -2 tool. Results Search strategy identified a total of 3 articles which met the inclusion criteria. The included studies investigated the impact of ERT on TMD occurrence and its related symptoms. The analysis revealed no significant association between ERT and TMD occurrence. A significant dose relationship was noted in one of the studies while another mentioned the possible relationship of TMD with educational status. Risk of bias among the studies was low, and the overall quality of evidence was deemed to be high. Conclusion This systematic review suggests that there is no conclusive evidence supporting an increased risk of TMDs among women receiving ERT. The findings indicate that ERT is unlikely to have a noticeable impact on TMDs. However, due to the limited number of studies available, further research is warranted to strengthen these conclusions and explore potential factors that may influence the relationship between ERT and TMDs.